2018
DOI: 10.21037/jss.2018.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Complications following single-level interbody fusion procedures: an ACS-NSQIP study

Abstract: Although numerous techniques can be utilized in the treatment approach to various lumbar pathologies, anterior approaches have an increased risk of developing a perioperative DVT and early mortality. Transfusion risk is more strongly associated with elevated American Society of Anesthesiologists (ASA) class, increased age, preoperative anemia, and patients with bleeding disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The complication and readmission rates reported in the literature vary between studies. Studies on the National Surgical Quality Improvement Program (NSQIP) database found a 5.51% readmission rate within 30 days [47] and a 4% major complication rate [48], similar to Chan et al, who reported a 3.5% 3-month readmission rate [49]. These rates are relatively similar to the readmission rate calculated for the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…The complication and readmission rates reported in the literature vary between studies. Studies on the National Surgical Quality Improvement Program (NSQIP) database found a 5.51% readmission rate within 30 days [47] and a 4% major complication rate [48], similar to Chan et al, who reported a 3.5% 3-month readmission rate [49]. These rates are relatively similar to the readmission rate calculated for the control group in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Good graft bed preparation, quality and quantity of bone graft blocks play important roles in intervertebral fusion. 9 , 10 With the clinical application of polyether ether ketone (PEEK) and nano-materials such as polyether ether ketone (PEEK) with elastic modulus equivalent to vertebral bone and good compatibility with tissue, some scholars use locally excised vertebrae. Plate articular process, vertebral body posterior margin hyperplasia, bone smashing into bone graft to obtain autologous bone particles to avoid iliac bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other investigators have examined blood transfusions in this setting and determined that transfusions were not associated with any complication differences between ALIF/direct lateral interbody fusions and PLIF/TLIF procedures. 36…”
Section: Blood Transfusionmentioning
confidence: 99%